2010
DOI: 10.1177/0091270009355158
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation and Biological Activity of the Oversulfated Chondroitin Sulfate Contaminant in Baxter Heparin

Abstract: From late December 2007 to February 2008, the number of adverse responses to heparin infusions rose noticeably above baseline levels in North America, ultimately resulting in a widespread recall of all heparin vial products made by Baxter Healthcare. Using various analytical techniques and the de novo synthesis of a fully sulfated chondroitin sulfate (FSCS) derivative, the authors have confirmed the identity of the contaminant as an oversulfated chondroitin sulfate (OSCS) and have also defined the heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…S2B). Consistent with our published observations that the heparins are not contaminated with OSCS alone (7,8); the published CE data (6,34) also showed that an OSHS co-migrated with heparin (see Ref. 6, supplemental Fig.…”
Section: Chemically Oversulfated Gags Were More Sulfated Thansupporting
confidence: 89%
See 2 more Smart Citations
“…S2B). Consistent with our published observations that the heparins are not contaminated with OSCS alone (7,8); the published CE data (6,34) also showed that an OSHS co-migrated with heparin (see Ref. 6, supplemental Fig.…”
Section: Chemically Oversulfated Gags Were More Sulfated Thansupporting
confidence: 89%
“…S9, last panel), and there are two heparin contaminant peaks that migrated before heparin in contaminated heparin by employing a high resolution CE method (see Ref. 34, Fig. 2).…”
Section: Chemically Oversulfated Gags Were More Sulfated Thanmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the symptoms and the known ability of dextran sulfate to activate the contact system [3], research quickly focused on OSCS mediated activation of the contact system as a prime biochemical mechanism to link contaminated heparin with the adverse events. In subsequent research, OSCS was found to activate the kallikrein-kinin (KK) pathway in human plasma and this pathway was proposed to cause the production of vasoactive mediators such as bradykinin (BK) and the anaphylatoxins C3a and C5a in a factor XIIa (FXIIa) dependent manner [4][5][6][7][8]. Consistent with this hypothesis, OSCS alone and OSCS contaminated heparin induced hypotension in swine or rat blood pressure models [4,5,7].…”
Section: Introductionmentioning
confidence: 81%
“…In subsequent research, OSCS was found to activate the kallikrein-kinin (KK) pathway in human plasma and this pathway was proposed to cause the production of vasoactive mediators such as bradykinin (BK) and the anaphylatoxins C3a and C5a in a factor XIIa (FXIIa) dependent manner [4][5][6][7][8]. Consistent with this hypothesis, OSCS alone and OSCS contaminated heparin induced hypotension in swine or rat blood pressure models [4,5,7]. Thus a model was proposed where OSCS facilitates the autocatalytic activation of FXII to FXIIa which in turn activates the conversion of plasma pre-KK to KK [9].…”
Section: Introductionmentioning
confidence: 99%